Facultad de Ciencias Administrativas de la UEB inauguró el I Seminario Internacional - García García, Mariana (2023)
The State University of Bolívar celebrates 34 years of autonomous life. In honor of this anniversary, the Faculty of Administrative Sciences, Business Management and Informatics organized the First International Seminar on Administrative Sciences, Technology, Communication and Tourism, from June 19 to 21, 2023.